Penilaian Risiko K3 Pekerjaan Enclosed Space Entry Pada Kapal Km. Sabuk Nusantara 40 Menggunakan Metode Job Safety Analysis Dan Bow Tie Risk Assesment - Jumrotin Nisa Lestari; Minto Basuki (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Work accidents that occur on ships often occur in various cases, one of which is a work accident that occurs in an enclosed space. This is often experienced by a crew member who is unable to understand the proper methods and procedures for working in an enclosed space. Against this background, the researcher conducted a risk assessment of personal safety when working in an enclosed space to find out the causes, impacts and controls of the crew members' lack of understanding and knowledge of personal safety when working in an enclosed space. In this descriptive study using the Job Safety Analysis (JSA) method and the Bowtie method, the researchers obtained very high/extreme (E) scores in carrying out work in closed spaces, namely the ship's crew inhaled poisoned air/gas while checking in the cofferdam tank where these results obtained an likelihood value of 66% and a severity value of 71%. By holding routine drills regarding the application of safety principles in an enclosed space in more detail to all Ship's Crew and at the end of the drill closing displays a training video that displays shows about various accidents that occurred in an enclosed space and the causes of these events are reviewed in detail. So with a more detailed drill on the application of safety principles regarding enclosed space material to all Ship's Crew, it is hoped that it can minimize the occurrence of work accidents in an enclosed space.